Class Discrimination vs. Racial Discrimination - Schiller, Bradley R. (The Review of Economics and Statistics, 1971)
W HILE the subject of racial discrimination has enjoyed considerable attention in the literature, a careful distinction between discrimination based on color and discrimination based on economic status of one's parents continues to be a rare event. This paper attempts to render that distinction more explicit by examining the relative socio-economic achievements of black and white children who were reared in families receiving public assistance. An examination of those achievements leads to the suggestion that the educational and early occupational handicaps imposed upon these lower class youths by reason of their impoverished economic origins are of the same kind and perhaps quantitatively as important as those handicaps attributable to racial discrimination. Thus, class discrimination is seen to be potentially as potent a force as is racial discrimination in limiting the attainments of poor youth. The basic data employed here are taken from a national sample of families who had received Aid to Families with Dependent Children (AFDC) up until the beginning of 1961.' The immediate focus of this inquiry is on the 1,653 male offspring of those families who were at least 16 years of age at the time of the interview (January-March 1961). Nearly all of these have completed their education and already embarked upon their occupational careers. Estimates of the relative impacts of class discrimination and racial discrimination are obtained by contrasting these educational and early occupational achievements of the white and black AFDC sons both to each other and to a representative cross section of the entire male population in the United States.